2016
DOI: 10.1038/ncomms12906
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule visualization of dynamic transitions of pore-forming peptides among multiple transmembrane positions

Abstract: Research on the dynamics of single-membrane proteins remains underdeveloped due to the lack of proper approaches that can probe in real time the protein's insertion depth in lipid bilayers. Here we report a single-molecule visualization method to track both vertical insertion and lateral diffusion of membrane proteins in supported lipid bilayers by exploiting the surface-induced fluorescence attenuation (SIFA) of fluorophores. The attenuation follows a d−4 dependency, where d is the fluorophore-to-surface dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 46 publications
5
51
0
Order By: Relevance
“…The results are in accordance with the expectation that the floppy ssDNA is in close proximity to the liposome surface, while the rigid dsDNA stands upright on the surface . We also applied LipoFRET to the LL‐37 peptide and obtained similar results as in our previous work on solid‐supported lipid bilayers (Supporting Information, Figure S5), further demonstrating the validation of LipoFRET.…”
Section: Figuresupporting
confidence: 89%
“…The results are in accordance with the expectation that the floppy ssDNA is in close proximity to the liposome surface, while the rigid dsDNA stands upright on the surface . We also applied LipoFRET to the LL‐37 peptide and obtained similar results as in our previous work on solid‐supported lipid bilayers (Supporting Information, Figure S5), further demonstrating the validation of LipoFRET.…”
Section: Figuresupporting
confidence: 89%
“…The high concentration of sterols in the outer leaflet of host cell membranes may also help prevent LL-37 from inserting into host cell membranes (15, 17). Previous work has shown that at sufficiently high concentration LL-37 not only permeabilizes the Escherichia coli OM and CM (11, 15, 16, 18, 19) but also induces oxidative stress (13).…”
mentioning
confidence: 99%
“…Furthermore, LL-37 synergizes with other host-derived airway antimicrobials in killing bacteria (e.g., defensins and lysozyme) (35,124,129,130). There are multiple posited mechanisms by which LL-37 directly kills bacterial cells: there is evidence in the literature for the carpet model of bacterial killing (131) as well as for a modified, toroidal pore-forming model (132,133), both of which compromise bacterial membrane integrity, resulting in lysis. There is additional evidence that LL-37 preferentially attacks septating (actively growing/dividing) bacterial cells, thereby inhibiting bacterial proliferation (134).…”
Section: Ll-37 An Antimicrobial Peptide With Bactericidal and Immunomentioning
confidence: 99%